2021
DOI: 10.3389/fphys.2021.710887
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Functional Characterization of Female Reproductive Fluids: A Report of the First Two Infants Born Following Addition of Their Mother's Fluids to the Embryo Culture Media

Abstract: Culture media supplemented with reproductive fluids (RF) have been used in livestock species, improving the efficiency and quality of in vitro produced embryos. However, usefulness in humans is still unknown. In this study, we collected human reproductive fluids (HRFs) ex vivo (from 25 patients undergoing abdominal hysterectomy plus bilateral salpingectomy) and in vivo (from 31 oocyte donors). Afterward, protocols to evaluate their osmolality, pH, total protein concentration, endotoxin level, and sterility wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In this species, we also created a biobank of reproductive fluids and have a small number of animals in a sanctuary to study their long-term health and the effects of assisted reproductive techniques. Finally, our group completed a preliminary human clinical trial in which the embryo recipient mothers themselves donated uterine fluid to be added to the medium for culturing their own embryos (Canha-Gouveia et al, 2021). As a result, the first two children from embryos developed in culture media containing their mother's own uterine fluid were born and we also established all the necessary regulatory and biosafety conditions to create a biobank of human reproductive fluids that can be used for future research (Figure 4).…”
Section: The Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In this species, we also created a biobank of reproductive fluids and have a small number of animals in a sanctuary to study their long-term health and the effects of assisted reproductive techniques. Finally, our group completed a preliminary human clinical trial in which the embryo recipient mothers themselves donated uterine fluid to be added to the medium for culturing their own embryos (Canha-Gouveia et al, 2021). As a result, the first two children from embryos developed in culture media containing their mother's own uterine fluid were born and we also established all the necessary regulatory and biosafety conditions to create a biobank of human reproductive fluids that can be used for future research (Figure 4).…”
Section: The Evidencementioning
confidence: 99%
“…In all three species, the fluids were collected ex vivo (slaughterhouse specimens in pigs and cows, surgically removed organs in women) or in vivo (transvaginal aspiration of endometrial fluid). The fluid volumes obtained were usually between 20 and 100 microlitres, depending on the organ and the species, and the samples were immediately transported to the laboratory, where purification by centrifugation and quality control tests were performed (Canha-Gouveia et al, 2021) before storing the different batches at the corresponding biobank (human or animal). In general, fluids are added to the culture media at ~1-2% v/v and all the mentioned pieces of evidence have been obtained under these conditions.…”
Section: The Evidencementioning
confidence: 99%
“…Coy and colleagues have shown that oviductal fluid, as well as specific proteins secreted by the oviduct, improve the rates of fertilization and embryonic development in vitro and in vivo, resulting in greater pregnancy rates and improved pregnancy outcomes with ART [110][111][112][113]. This technology holds great potential to overcome poor fertility and also to maximize the impact of elite genetic stock, and thus to dramatically improve the efficiency of livestock production.…”
Section: Reproductive Fluidsmentioning
confidence: 99%